The cultural betrayal of Black women and girls : a Black feminist approach to healing from sexual abuse - Gómez, Jennifer M. (American Psychological Association, 2023)
"This book provides a theoretical framework for empirically examining the impact of violence on marginalized peoples across the lifespan. With anti-Black racism uniquely impacting Black women and girls who are sexually victimized, a unifying, empirically testable framework with a critical race perspective to examine Black women and girls' experiences of sexual violence is warranted. Dr. Jennifer M. Gómez created cultural betrayal trauma theory (CBTT) to expand the limiting assumption in the dominant theoretical and methodological literature on the impact of violence that traumas, such as rape, are solely interpersonal. In CBTT, Dr. Gómez builds on Black feminist scholarship, ethnic minority trauma psychology, and betrayal trauma theory to provide a theoretical framework for examining the impact of violence on marginalized peoples across the lifespan.The Cultural Betrayal of Black Women and Girls is the first book to use the CBTT research to contribute to academic and national discussions regarding anti-Black racism and sexual abuse. Using CBTT as a foundation, this book incorporates transdisciplinary scholarship on racism, intersectional oppression and intersectionality, sexual abuse against Black women and girls, cultural competency and critical consciousness in therapy, and healing in the community into a single resource for understanding and addressing oppression and sexual abuse on individual, institutional, and societal levels."--